Perkembangan Sosial Emosional Anak Usia Dasar di Lingkungan Keluarga - Ruja Wati (PALAPA, 2020)
Children in a family environment that is less harmonious, the most important thing the child expresses is feelings of anger or sadness when someone asks it and this will affect the social to others. Therefore it is necessary to have an environment that is able to direct the child's social emotional direction in a positive direction. the family environment is very influential on the child's social emotional, when the child is in the family environment such as conflicts between families, lack of communication in the family, and so on actually the child's emotional emotional needs are not met. So the focus of problem is how elementary age children must have a good social emotional that is by providing a good environment as well as parenting parents themselves. For this reason the approach used is a qualitative approach with the method of field study with the data collection technique is interview. According to data in the field that the social emotional development of children who are socially emotionally good are parents giving examples, advice and examples from their own environment that show the goodness of kindness. And give examples of examples in daily life such as greeting, being honest and not distinguishing friends. So that children's emotions can be controlled well because they are always careful and not selfish, which later gives birth to good social towards parents, siblings and even peer friends.